From Biting to Hugging : Understanding Social Development in Infants and Toddlers. - Wittmer, Donna; Clauson, Deanna W. (Newburyport : Gryphon House Inc., 2018)
With the increase in both parents working outside the home during the last two decades, infants and toddlers are spending more time together in infant/toddler programs and family child-care homes. From Biting to Hugging will give you effective strategies to help you take advantage of this peer time.
The many reasons to focus on social development with peers in the early year -- So much more than parallel play-foundations of infant and toddler relationships -- Strategies for supporting infant and toddler relationships -- The caring capacities-being prosocial, hugs with friends, and having fun -- Strategies for supporting the caring capacities -- Peer conflicts-struggles and learning -- Strategies for supporting children in resolving peer conflicts -- Children who feel particularly challenged with peer relationships -- Strategies for supporting children who feel challenged by peer relationships.
Print version record.
Includes bibliographical references (pages 164-179) and index.
eBooks on EBSCOhost
Keywords: Early childhood education -- Social aspects; Social interaction in infants; Social interaction in children; Infants -- Development; Toddlers -- Development; Éducation de la première enfance -- Aspect social; Interaction sociale chez le nourrisson; Interaction sociale chez l'enfant.; Nourrissons -- Développement.; Tout-petits -- Développement.; EDUCATION -- Elementary; Early childhood education -- Social aspects; Infants -- Development; Social interaction in children; Social interaction in infants; Toddlers -- Development